First Resolution of Microlensed Images of a Binary-lens Event - Zexuan Wu; Subo Dong; A. Mérand; Christopher S. Kochanek; Przemek Mróz; Jinyi Shangguan; Grant Christie; Thiam-Guan Tan; Thomas Bensby; Joss Bland-Hawthorn; Sven Buder; Frank Eisenhauer; et al. (The Astrophysical Journal)
We resolve the multiple images of the binary-lens microlensing event ASASSN-22av using the GRAVITY instrument of the Very Large Telescope Interferometer (VLTI). The light curves show weak binary-lens perturbations, complicating the analysis, but the joint modeling with the VLTI data breaks several degeneracies, arriving at a strongly favored solution. Thanks to precise measurements of the angular Einstein radius θ _E = 0.724 ± 0.002 mas and microlens parallax, we determine that the lens system consists of two M dwarfs with masses of M _1 = 0.258 ± 0.008 M _⊙ and M _2 = 0.130 ± 0.007 M _⊙ , a projected separation of r _⊥ = 6.83 ± 0.31 au, and a distance of D _L = 2.29 ± 0.08 kpc. The successful VLTI observations of ASASSN-22av open up a new path for studying intermediate-separation (i.e., a few astronomical units) stellar-mass binaries, including those containing dark compact objects such as neutron stars and stellar-mass black holes.